Epidemiological Peculiarities of the Flu Epidemic of 2016 in St. Petersburg - L. S. Karpova; N. M. Popovtseva; T. P. Stolyarova; K. A. Stolyarov; O. S. Konshina; A. A. Sominina (Эпидемиология и вакцинопрофилактика)
To identify the peculiarities of manifestation of epidemic process of influenza in 2016, and causes high morbidity and mortality in St. Petersburg, a comparative analysis of the incidence of influenza and acute respiratory viral infections, hospitalization and mortality in children and adults during the epidemic of 2016 in St. Petersburg and other 58 the observed cities of the Russian Federation. The epidemic of 2016 in St. Petersburg from other cities were characterized by a greater intensity: the duration of the epidemic; the incidence of the population on the peak (at 1.9 and 1.3%), within the boundaries of the epidemic in the city (7.7 and 5.4%) and the country (11.9 and 9,6%); shares admitted to hospital with a diagnosis of «influenza» among the whole population (17.1 and 14,0%); greater mortality from influenza among the whole population (3.3 tims), persons 15 - 64 (in 3 times) and 65 years and older (2.8 times). The low level of population immunity in Saint-Petersburg in the before the epidemic period and lower frequency of hospitalization of patients with influenza and ARVI among the population as a whole (2.4% and 3.6 percent), particularly children and persons over 65 years of age (2 times), could be the cause of high morbidity and mortality from influenza in St. Petersburg.